Patriot games: eating out of the foreign hand - Subrahmanyam, K. (2001)
This article accepts the fact that few countries are free from the scourge of political corruption. However, this rationalization overlooks the fact that India is targeted by an adversary sworn to its disintegration. Therefore, the nexus of narcotics, organized crime and money laundering needs to be thoroughly probed and examined from the point of view of India's security interests. - Reproduced.
Keywords: State security